CCL3L1 copy number and susceptibility to malaria - Carpenter, Danielle; Färnert, Anna; Ingegard, Rooth; Armour, John A.L.; Shaw, Marie-Anne (Elsevier, 2012)
Copy number variation can contribute to the variation observed in susceptibility to complex diseases. Here we present the first study to investigate copy number variation of the chemokine gene CCL3L1 with susceptibility to malaria. We present a family-based genetic analysis of a Tanzanian population (n = 922), using parasite load, mean number of clinical infections of malaria and haemoglobin levels as phenotypes. Copy number of CCL3L1 was measured using the paralogue ratio test (PRT) and the dataset exhibited copy numbers ranging between 1 and 10 copies per diploid genome (pdg). Association between copy number and phenotypes was assessed. Furthermore, we were able to identify copy number haplotypes in some families, using microsatellites within the copy variable region, for transmission disequilibrium testing. We identified a high level of copy number haplotype diversity and find some evidence for an association of low CCL3L1 copy number with protection from anaemia.